Exploration of Influential Factors in Infrastructure Profit Dynamics - Mubarok, Faizul; Benbadri, Asir Filard; Erlin, Erlin; Henanda, Fauzan Falah (FEB Universitas Sultan Ageng Tirtayasa, 2024)
Profitability ratios help evaluate a company's profitability and the efficacy of its management. Financial managers who grasp the factors that impact profitability can enhance their company's profitsThis research investigates the impact of capital structure, liquidity, sales growth, company size, working capital turnover, and profitability on six infrastructure companies listed on the Indonesia Stock Exchange between 2017 and 2022. The companies were chosen using purposive sampling techniques, and the profitability was analyzed using panel data regression analysis with a fixed effect model. The study results demonstrate that all variables have a significant impact on the profitability of infrastructure companies. Financial managers can make better financial decisions and optimize performance by understanding these factors. This research yields valuable insights into the factors influencing profitability within Indonesia's infrastructure industry, thereby offering significant benefits to stakeholders.